Diabetes Mellitus as a Predictive Factor for Urinary Tract Infection for Patients Treated with Kidney Transplantation - Kaori Ozawa; Manabu Takai; Tomoki Taniguchi; Makoto Kawase; Shinichi Takeuchi; Kota Kawase; Daiki Kato; Koji Iinuma; Keita Nakane; Takuya Koie (Medicina, 2022)
Background and Objectives: We aimed to investigate the rate of incidence and risk factors of post-transplant urinary tract infection (UTI) in patients receiving kidney transplantation (KT) at our institution. Materials and Methods: A retrospective cohort study was carried out on patients who underwent KT for end-stage kidney disease (ESKD) from January 2008 to December 2021 at Gifu University Hospital. UTI was defined as the existence of bacterial and/or fungal infection in urine with ≥105 colony-forming units/mL, with or without urinary and/or systemic symptoms of UTI. Patients were divided into two groups: those with UTI after KT (UTI group) and those without UTI (non-UTI group). The primary endpoint of this study was the relationship between covariates and UTI after KT. Results: Two hundred and forty patients with ESKD received KT at Gifu University Hospital. Thirty-four participants developed UTI after surgery, and the most common pathogen was Escherichia coli. At the end of the follow-up, graft loss was observed in six patients (2.5%), independent of UTI episodes. In the multivariate analysis, diabetes mellitus (DM) was statistically associated with post-transplant UTI in kidney transplant recipients. Conclusions: Preoperative serum glucose control in patients with DM may have a crucial role in preventing UTI and preserving renal function after KT.